Enhancing Cr(VI) bio-reduction by conductive materials and enrichment of functional microbes under anaerobic conditions. (January 2022) - Chen, Fang; Lei, Pan; He, Peng; Gu, Chunyao; Chen, Yaozong; Zhang, Ke; Zhu, Jianyu; Gan, Min
Abstract: A few studies reported the impact of mineral conductivity properties on contaminant-mineral-microbe interactions and microbial community structure changes in the interaction process. To fill the gap, conductive minerals (magnetite/hematite) and an insulative mineral (quartz) were introduced into Cr(VI) reduction systems to investigate the effect of mineral conductivity properties on Cr(VI) removal. Results showed that conductive minerals enhanced Cr(VI) reduction rate as compared to insulative minerals. Higher reduction percentage (>86%) was observed when both ERB (extracellular respiratory bacteria) and conductive minerals were presence than those with only minerals (<10%) or ERB (<55%), indicating a synergistic effect existed in this bio-remediation system. Moreover, surface elements detection manifested higher Fe-containing groups and Fe(III)-Cr(III) complexes covered on conductive minerals surface when ERB was present. Electrochemical data suggested that ERB facilitated the activity of electron transference on the surface of conductive minerals. Our results indicated that conductive minerals did act as an "electron shuttle" while insulative minerals increased adsorption sites to accelerate Cr(VI) reduction. 16S rRNA sequences results demonstrated that conductive minerals changed the microbial community structure and increased the diversity of the functional microbes including Pseudomonas spp. and Exiguobacterium spp. This work is of deep significance for better understanding the process of elements biogeochemical and elimination of pollutants. Graphical abstract: Image 1 Highlights: Synergistic effect of ERB and conductive minerals enhanced Cr(VI) reduction rates. More Fe-containing groups covered on conductive mineral surface when ERB presence. ERB facilitated electron transference on the surface of conductive minerals. Conductive minerals changed the microbial community structure. Conductive minerals increased the diversity of functional microbes ( Pseudomonas ).